Meningkatkan Branding SDN Pengkok 04 dalam Membuat Profil Sekolah dengan Akun Instagram Berbantuan Aplikasi Canva for Education - Septyana Candra Puspita; Dewi Anjarsari; Qoni’ah Al Munasiroh (Jurnal Nusantara Berbakti, 2025)
The development of Information and Communication Technology and the demands of 21st century teachers have provided new innovations to support promotion in branding school institutions. Technology is one way that can be used as a promotional media to make it easier for the public to assess schools. This community service activity aims to improve the branding of SDN Pengkok 04 in creating a school profile with an Instagram account assisted by the Canva for Education application. This community service activity was carried out at SDN Pengkok 04 Sragen with 9 teachers. The result was that all teachers made pamphlets using Canva for Education. In order for teachers' abilities to be maximized in their use, teachers must continue to practice independently using Canva for Education or other applications that support school promotion and pass on the skills they have acquired to other teachers.